Supplement to the Code of Virginia 377, tit. 52, ch. 184, § 3780 (1898) - (:unkn) unknown (My University, 1895)
Prohibited the carrying of a concealed pistol, dirk, Bowie knife, razor, slungshot, or any weapon of the like kind. Punishable by fine of $20-100 and forfeiture of the weapon.
Keywords: CARRY - CONCEALED